The Role Of Media In The United States Environmental Diplomacy: A Case Study Of Oil-Spill Disaster In Deepwater Horizon Film - Robertua, Verdinand; Josua H. Silitonga , Immanuel (Department of International Relations Universitas Pertamina, 2021)
The Deepwater Horizon Oil-Spill is the most disastrous environmental pollution event in America's history. The film Deepwater Horizon, which takes the title exactly matches the name of the incident, explains the backgrounds of the catastrophe. This film shows that the accident occurred due to the negligence of British Petroleum as a company that manages the Deepwater Horizon rig. To reveal the role of the film in United States environmental diplomacy, the researcher will use the Deepwater Horizon film as a case study and the concept of environmental diplomacy as a unit and research analysis tool. This study uses qualitative research methods with data collection techniques, such as literature surveys and observations. This research argues that media is an essential component that plays a role in environmental diplomacy.